ANALISIS TAX PLANNING ATAS RESTITUSI PAJAK PERTAMBAHAN NILAI (STUDI KASUS NINDYA PRANA KSO) - Rivai Arvan RZ; Anggi Pratama Nasution; Mika Debora Barus (Ensiklopedia Education Review, 2022)
This study aims to determine the effort of tax planning for VAT refunds to minimize correction and penalty by the Tax Auditor. The research object used was Nindya Prana KSO and the method used in this study was descriptive with a qualitative approach by visiting companies directly and conducting observations, documentation, as well as direct interviews with company staff to ask for information. From the analysis it is known that Nindya Prana KSO conducts tax planning with the Taxation Law.Keywords: VAT Restitution, Tax Planning